Urgensi Neuroscience dalam Pendidikan (Sebagai langkah inovasi Pembelajaran) - nurasiah, Nurasiah (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Various studies on dasyhatnya art learning relationship can affect the development of intelligence can presumably provide learning solutions either at home, school, and community. Education should be able to provide the brain experiences of learners. Several studies on nerve cells in the human brain, nerve cells can grow and develop through the medium of art, every art form involves multiple tissues in brain cells. The brain is not static body elements, which have become so can not be changed. Learning the art of influencing the development of emotional, spiritual, and cultural more than intelligence apart from cognitive intelligence. The type of art that is recommended can affect the brain development of learners and emotional intelligence is the art of music (piano and organ), dance, and painting. Intelligence can help the art of thinking and working learners.